Tropisetron attenuates amyloid‐beta‐induced inflammatory and apoptotic responses in rats. (13th August 2013) - Rahimian, Reza; Fakhfouri, Gohar; Ejtemaei Mehr, Shahram; Ghia, Jean‐Eric; Genazzani, Armando A.; Payandemehr, Borna; Dehpour, Ahmad Reza; Mousavizadeh, Kazem; Lim, Dmitry
Abstract Background Alzheimer's disease (AD) is a neurodegenerative disorder featured by deposition of beta‐amyloid (Aβ) plaques in the hippocampus and associated cortices and progressive cognitive decline. Tropisetron, a selective 5‐HT3 receptor antagonist, is conventionally used to counteract chemotherapy‐induced emesis. Recent investigations describe antiphlogistic properties for tropisetron. It has been shown that tropisetron protects against rat embolic stroke. We investigated protective properties of tropisetron in a beta‐amyloid (Aβ) rat model of AD and possible involvement of 5‐HT3 receptors. Material and methods Aβ (1–42) was injected into the hippocampus of male rats. Animals were treated intracerebroventricularly with tropisetron, mCPBG (selective 5‐HT3 receptor agonist) or mCPBG plus tropisetron on days 1, 3, 5 and 7. Seven days following Aβ administration, inflammatory markers (TNF‐α, COX‐2, iNOS and NF‐κB), apoptotic markers (caspase 3 cytochrome c release) and calcineurin phosphatase activity were assessed in hippocampus. Results Seven days following Aβ inoculation, control animals displayed dramatic increase in TNF‐α, COX‐2, iNOS, NF‐κB, active caspase 3, cytochrome c release and calcineurin phosphatase activity in the hippocampus. Tropisetron significantly diminished the elevated levels of these markers and reversed the cognitive deficit. Interestingly, tropisetron was also found to be a potent inhibitor of calcineurin phosphatase activity. The selective 5‐HT3 receptor agonist mCPBG, when co‐administered with tropisetron, completely reversed the procognitive and anti‐apoptotic properties of tropisetron while it could only partially counteract the anti‐inflammatory effects. mCPBG alone significantly aggravated Aβ‐induced injury. Conclusion Our findings indicate that tropisetron protects against Aβ‐induced neurotoxicity in vivo through both 5‐HT3 receptor‐dependent and independent pathways.